Dileclion of pathogenic bacteria and mycoplasmas from pneumonic lungs of pigs and histopalhological finding - Siti Chotiah; Sobironingsih . (Indonesian Center for Animal Research and Development (ICARD), 1996)
A total of 104 pig's lung samples with pneumonic lesions were collected from Kapuk abattoir in West Jakarta and piggeries in Tangerang, West Java. Isolation and identification of pathogenic bacteria and mycoplasmas of the lung were carried out and Mycoplarma sp . was isolated from 9 (8.7%) samples, Pacteurella multocida from 5 (4.8%)samples, and Bordetella brornrhiseptica from 2 (1 .9%) samples while the test of the samples were negative . Histopathological examination were also carried out and the lesions were found on 30 (28.8%) samples for Bordetella sp., 6 (5 .8%) samples for Mycoplarma sp ., 16 (15.4%) samples for Mycoplarma sp . in combination with Bordetella sp ., 25 (24.0%) samples for Mycoplavma sp . in combination with Pacteurella sp. and 27 (26.0 %) samples were judged to be normal . All microorganisms were found 68 .7% and 72.7% from apical lobes of the lung by bacteriological and histopathological examinations respectively . Keywords: Mycoplavma sp ., Pacteurella nrulttwida, Bordetella brimrhiseprica, pneumonia, pig